Differentiating Learning in the ESP Class for IT-sphere University Students. - Tonenchuk, Tetiana (My University, 2023)
In the differentiated lesson, the teacher takes account of the students’ levels, abilities, interests, and needs. Effective differentiation includes ensuring student access to information, materials, and support; giving useful feedback; being a positive presence in the student's life. Differentiation requires not only the development of a comprehensive plan for how to use resources and how much time it takes to facilitate differentiated learning, but also developing strategies and criteria to assess results, which might be a subject of further research.
Keywords: differentiating; ESP